Investigation of fuel cell output under different electrolyte conditions and renewable hydrogen generation source from Teluk Batik, Malaysia - Osman Shah, Shaffiq Zainal; Zashidi, Muhammad Azmi; Zulkifli, Muhamad Amirul Hazami; Ramli, Mohamad Aidil (2025)
Proton exchange membrane fuel cells (PEMFCs) represent a promising clean energy technology, providing an efficient and environmentally sustainable method of electricity generation through electrochemical reactions. The performance and efficiency of PEMFCs are strongly influenced by several parameters, including electrolyte type and concentration, operating temperature, input voltage, and the source of water used for electrolysis. Optimising PEMFC systems requires a comprehensive understanding of how these factors interact, particularly in relation to the application of non-conventional electrolytes and renewable water sources for hydrogen production. This study investigates the performance of PEMFCs under different electrolyte conditions (HCl and NaOH), renewable water sources such as seawater, and applied input voltages (5 V, 10 V, 15 V). The experimental design further examined the effects of different electrolytes with 0.5 M concentration and operating temperatures (room temperature, 70 °C, 80 °C, and 90 °C) on output voltage. Results demonstrate that electrolyte concentration, temperature, water source, and input voltage exert a significant influence on PEMFC efficiency and power output. Specifically, higher NaOH concentrations [0.5 M], elevated temperatures (90 °C), and greater applied voltages (15 V) enhanced hydrogen generation and overall cell performance. In contrast, the use of nondistilled water sources such as seawater was associated with reduced efficiency. These findings provide valuable insights into optimising PEMFC systems for sustainable energy production, particularly when integrating renewable water resources and non-traditional electrolytes.